2006
DOI: 10.1007/s00442-006-0522-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of metabolism with tissue carbon and nitrogen turnover rate in small mammals

Abstract: Stable isotopes have proven to be a useful tool for deciphering food webs, examining migration patterns and determining nutrient resource allocation. In order to increase the descriptive power of isotopes, an increasing number of studies are using them to model tissue turnover. However, these studies have, mostly by necessity, been largely limited to laboratory experiments and the demand for an easier method of estimating tissue turnover in the field for a large variety of organisms remains. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 53 publications
(70 reference statements)
7
126
2
Order By: Relevance
“…2 & 3), which indicates that the tissue turnover might be attributable to both tissue replacement in the form of metabolism (m) and net tissue increase in the form of growth (k). Metabolic contributions to nitrogen isotopic turnover reached approximately 70−77% and 39−47% for liver and muscle, respectively, while 86−90% contribution of growth to nitrogen isotopic turnover was strongly correlated with less metabolic activity of gill, and reflected that growth played a more important role in the long-term isotopic turnover of gill (Tables 2 & 3 Previous studies have demonstrated that the discrepancy in turnover rates between tissues is mainly driven by variable metabolic contributions to the isotopic turnover process (Arneson & MacAvoy 2005, MacAvoy et al 2006. The relative importance of metabolism versus growth in nitrogen isotopic turnover is determined by bioenergetic allocations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…2 & 3), which indicates that the tissue turnover might be attributable to both tissue replacement in the form of metabolism (m) and net tissue increase in the form of growth (k). Metabolic contributions to nitrogen isotopic turnover reached approximately 70−77% and 39−47% for liver and muscle, respectively, while 86−90% contribution of growth to nitrogen isotopic turnover was strongly correlated with less metabolic activity of gill, and reflected that growth played a more important role in the long-term isotopic turnover of gill (Tables 2 & 3 Previous studies have demonstrated that the discrepancy in turnover rates between tissues is mainly driven by variable metabolic contributions to the isotopic turnover process (Arneson & MacAvoy 2005, MacAvoy et al 2006. The relative importance of metabolism versus growth in nitrogen isotopic turnover is determined by bioenergetic allocations.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have demonstrated that the discrepancy in turnover rates between tissues is mainly driven by variable metabolic contributions to the isotopic turnover process (Arneson & MacAvoy 2005, MacAvoy et al 2006. The relative importance of metabolism versus growth in nitrogen isotopic turnover is determined by bioenergetic allocations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the discrepancies of turnover rates between tissues were mainly driven by variable metabolic contributions to the turnover process. EvansOgden et al (2004), Arneson & MacAvoy (2005) and MacAvoy et al (2006) all suggested that the carbon isotopic turnover rates were correlated strongly with the metabolic rate of tissue involved. The faster the metabolism, the quicker the turnover rate and therefore the shorter the half-life of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The growth rate constant, k, was estimated by fitting an exponential growth model to observed weight data, k =log(final weight/initial weight)/time(d), while parameter m was obtained using iterative non-linear regression. Coefficients k and m provide an indicator of the time period necessary for half of the muscle nitrogen to be replaced by new nitrogen after animals consume a new diet (half life, t 50 ) (MacAvoy et al 2006).…”
Section: Estimation Of Nutrient Contribution and Nitrogen Half Lives mentioning
confidence: 99%